Expérience d'immigration de Francophones en contexte linguistique minoritaire au Canada : défis et répercussions sur la santé mentale - Archambault, Hélène; de Moissac, Danielle; Levesque, Annabel; Kinkumba, Babou; Gueye, Ndeye Rokhaya; Tempier, Raymond; Alimezelli, Hubert Tote (Reflets, 2021)
Cet article explore les défis rencontrés par de nouveaux arrivants francophones à leur arrivée dans une communauté francophone en situation minoritaire au Canada, les répercussions qui en découlent et les facteurs modérateurs ayant une incidence sur leur intégration. Une recherche qualitative par entrevues semi-dirigées a été menée dans trois villes canadiennes auprès de soixante adultes immigrants ou réfugiés. Le défi principal auquel sont confrontées ces personnes est la barrière linguistique ; elle vient amplifier les défis liés à l’intégration sociale et la recherche de l’emploi. L’expérience migratoire a aussi une répercussion sur la santé mentale, sur les relations avec les proches et sur la santé physique. Le soutien social et la résilience personnelle favorisent l’adaptation dans la communauté d’accueil. Mots-clés : immigration, francophones, intégration, contexte linguistique minoritaire

Quête de caractérisation des profils pathologiques, itinéraires thérapeutiques et implications, sur les immigrants chez les CLOSM - Bahi, Boniface; Macleod, Andrea; Kamin, Mireille; Lamba, Moise; Vincent, Denis; Gaudet, Lyne; Dion, Michelle (University of Alberta, Campus Saint-Jean et Réseau Santé Alberta, 2024)
Ce projet de recherche piloté par le Réseau santé Alberta, en collaboration avec plusieurs directions régionales francophones de santé, s’est proposé d’étudier les enjeux de santé des immigrants francophones installés en Alberta, en Saskatchewan, au Yukon, dans les Territoires du Nord-Ouest, au Nunavut et en Terre-Neuve-et-Labrador, en référence aux déterminants sociaux de la santé et aux iniquités de santé perçues par ces francophones en situation minoritaire. Dans le but d’obtenir un aperçu général des enjeux rencontrés par ces francophones en situation minoritaire, cette étude a été réalisée afin de déceler un portrait global des défis de santé que rencontrent les francophones des régions ci-haut citées, à savoir les profils caractéristiques des pathologies émergentes de la population immigrante, les voies et moyens utilisés par ces immigrants pour pallier les difficultés liées et enfin, l’impact sur l’utilisation des services canadiens de santé des régions en question. En clair, chercher à identifier la nature de la pression de cette demande sanitaire immigrante. Entre autres, notre étude a un versant d’approche que nous indiquons comme épistémologies sanitaires comparées, relatives à des observations non participatives des phénomènes couramment vécus au sein des immigrants, qui arrivent au Canada dans un état de bonne santé, dans l’ensemble. Ils développent des maladies qu’ils n’avaient pas dans leurs conditions pré-migratoires, mais qui apparaissent avec le temps de vie au Canada. Les analyses documentaires, et notre sous-approche d’épistémologies sanitaires comparées liées aux études et des publications scientifiques antérieures portant sur les problèmes de santé des immigrants en général, et des francophones immigrants en situation minoritaire en particulier, aident à valider les données d’enquête. Celles-ci reposent sur les journaux de terrains professionnels des médecins de l’équipe de la recherche et de leurs réseaux de santé. Seules les études qui ont présenté une démarche scientifique et qui se sont appuyées sur des données empiriques, et celles se fondant sur une démonstration théorique, soit sur un modèle conceptuel ou sur une réflexion théorique, ont été retenues dans notre base documentaire analysée. Ces données s’ajoutent aux informations des 100 cas immigrants, et de celles des 25 professionnels des régions de l’étude. Les synthèses des informations permettent de soutenir que : - Les immigrants récemment arrivés au Canada ont un état de santé positif par rapports aux non immigrants canadiens - Cette santé se détériore au fur et à mesure que l’immigrant réside longtemps au Canada, à travers un mode de vie d’adhésion à de nouvelles habitudes de vie, en termes alimentaires et de relations sociales plus ou moins enviables, surtout, suivant les offres de possibilité ou non du milieu de vie canadien. - La santé mentale et les maladies chroniques font partie des états de morbidité (pathologies) que ces immigrants développent, comme expression de dégradation de leur santé. Une cause qui fédère la plupart des causes sectorielles, est le stress négatif qui surgit de l’écart entre les aspirations ou attentes pré-migratoires et ce que la réalité post-migratoire, la quotidienneté canadienne offre ou impose aux individus et aux groupes. - De ce qui précède, découlent des dysfonctionnements familiaux aux conséquences ou méfaits de tous ordres : liens conjugaux pathogéniques et conflictuels, liens filiaux (rapports parents-enfants) avec inversion d’autorité, etc… - Être immigrant et francophone limite l’accès aux services de santé pour des raisons linguistiques et d’offre rare de services spécialisés de santé correspondant à leur demande sanitaire, ce qui implique une prise en charge moindre de leurs problèmes de santé. C’est un processus cumulatif d’aggravation, voire de chronicisation de certains états pathologiques. - Les barrières linguistiques et la plupart des difficultés d’accès aux soins de santé qui en découlent constituent des principaux facteurs qui perpétuent les inégalités de santé perçues par les immigrants francophones en situation minoritaire par rapport à leurs homologues immigrants anglophones - Les francophones éprouvent des difficultés de santé liées, non seulement au fait de vivre dans un milieu linguistique minoritaire, mais, aussi, au fait d’être immigrant et de vivre dans un nouvel environnement avec une culture d’origine différente de celle de sa communauté d’accueil. - Beaucoup d’immigrants sont en quête de ressources humaines de santé homo-ethniques. En d’autres termes, ils vont à la recherche de thérapeutes de même origine ethnique. C’est ici que des églises évangéliques entrent en compte dans les itinéraires thérapeutiques. De part ces horizons sanitaires, des sphères pour la suite de la recherche, en termes de caractérisation de programmes d’intervention, se dessinent, en tenant compte des lacunes et besoins identifiés dans les services de soins de santé spécifiques aux immigrants. Des axes d’actions sont à envisager, en se fondant sur les principes de la Charte d’Ottawa (1986 et 2011) continuée par la Charte de Shanghai (2016). Les besoins sanitaires des immigrants sont en convergence avec ceux existants des populations francophones minoritaires qui les accueillent.

Poids, santé générale et santé mentale : la situation de divers sous-groupes d'immigrants au Canada - Bergeron, Pascale; Auger, Nathalie; Hamel, Denis (Revue canadienne de santé publique, 2009)
Contexte Au Canada, l’immigrant récent est souvent en meilleure santé que le non-immigrant. L’état de santé des sous-groupes d’immigrants (ethniques, culturels, linguistiques) est moins bien connu. Méthode En utilisant des données de l’Enquête sur la santé dans les collectivités canadiennes 2005 (Cycle 3.1), les associations entre trois caractéristiques des immigrants (1-temps écoulé depuis l’immigration, 2-être une minorité visible, 3-parler une langue officielle) et trois indicateurs de santé (1-santé générale perçue, 2-santé mentale perçue, 3-indice de masse corporelle (IMC)) ont été modélisées à l’aide de régressions logistiques multiples pour les immigrants des régions métropolitaines de recensement de Montréal, Toronto et Vancouver. Elles ont été ajustées pour des facteurs sociodémographiques. Résultats Les immigrants récemment arrivés qui appartiennent à une minorité visible sont moins susceptibles d’avoir une mauvaise santé perçue, tant générale (RC 0,72; IC95 % 0,54–0,97) que mentale (RC 0,64; IC95 % 0,43–0,96) et un IMC≥25 (RC 0,51; IC95 % 0,43–0,61) que les non-immigrants. Ceux qui n’appartiennent pas à une minorité visible ne présentent pas ces associations. Les immigrants qui ne parlent pas une langue officielle sont plus susceptibles d’avoir une mauvaise santé générale perçue (RC 1,49; IC95 % 1,06–2,10) que les non-immigrants. À Toronto et Vancouver, les immigrants tendent à être associés à un IMC moindre que les non-immigrants alors que ce n’est pas le cas à Montréal. Conclusion Cette étude témoigne de la présence du phénomène de l’immigrant en bonne santé au Canada mais démontre qu’une grande variabilité existe entre les sous-groupes d’immigrants. Ces constats sont importants pour une planification adéquate des services aux immigrants.

Multilingualism (but not always bilingualism) delays the onset of Alzheimer disease: Evidence from a bilingual community - Chertkow, Howard; Whitehead, Victor; Phillips, Natalie; Wolfson, Christina; Atherton, Julie; Bergman, Howard (Alzheimer Disease and Associated Disorders, 2010)
A recent paper by Bialystok et al in Neuropsychologia (vol. 45, pgs. 459 to 464) suggested that early bilingualism produced a statistically significant 4.1-year delay in onset of memory loss symptoms in older individuals with Alzheimer disease, possibly reflecting an increase in the cognitive reserve of these individuals. That study focused on multilingual elderly patients of whom 90% were immigrants. Our memory clinic, in Montreal Canada, has the advantage of having a large set of individuals who are either multilingual immigrants to Canada, or who are nonimmigrants but raised in both official languages of Canada—French and English. We thus attempted to replicate the above findings using a larger cohort in a different setting. We examined age at diagnosis of Alzheimer disease and age at symptom onset for all unilingual versus multilingual participants, and then for those who were nonimmigrant English/French bilinguals. Overall, we found a small but significant protective effect of more than 2 languages spoken, but we found no significant benefit in bilinguals overall in relation to age at diagnosis or age at symptom onset. However, in the immigrant group, the results mirrored those of Bialystok et al with 2 or more languages delaying the diagnosis of Alzheimer disease by almost 5 years. A trend toward the same effect was also seen in nonimmigrants whose first language was French. In contrast, in nonimmigrants whose first language was English, no such effect was found. These results are discussed in relation to the earlier findings and the theory of cognitive reserve.

Repérage de quelques obstacles linguistiques et culturels des soins de santé pour les immigrants francophones de la Nouvelle-Écosse - Fontaine, Louise (Port Acadie, 2010)
Ce texte s’attarde au concept d’« immigrant francophone » appliqué au contexte de la Nouvelle-Écosse. Contrairement à ce qu’on peut imaginer à un premier niveau d’analyse, ce concept est polysémique et le sens qu’on y attribue varie selon les acteurs sociaux qui l’utilisent. Donc, afin de mieux délimiter l’objet de notre propos, nous avançons quelques éléments de définition à prendre en compte. Il s’agit d’une recherche exploratoire orientée vers la formulation de quelques pistes de réflexion, voire quelques hypothèses de travail à vérifier lors de la réalisation de futures recherches dans le domaine de la santé auprès des communautés francophones et acadiennes de la Nouvelle-Écosse. Pour étoffer notre propos, nous présentons quelques données empiriques recueillies à même le travail de terrain mené principalement dans le milieu associatif à Halifax et dans le sud-ouest de la province depuis 2003. Dans ce contexte, nous avons mené des enquêtes en procédant notamment à de l’observation participante. Nous avons aussi eu recours à des documents écrits tels que des documents gouvernementaux, des articles dans des revues spécialisées, des journaux. Les liens que nous avons établis entre des thèmes comme langue, culture et santé nous ont conduite finalement à proposer quelques questions de recherche et quelques hypothèses de travail.

Gaps in knowledge and practices of malaria prevention in Francophone African immigrants in Metropolitan Edmonton - Hanna, Taylor A.; Ahmed, Ali; Vincent, Rémi; Coulibaly, Kongnon Sangué; Ahmed, Youssef; Petrick, Ryland; Vincent, Etienne; El Hafid, Mélanie; Hawkes, Michel T.; Ravi, Srilata; Gnidehou, Sedami (Malaria Journal, 2022)
Background Important knowledge gaps exist in the understanding of the management of the risks of imported malaria in Canada among Francophone immigrants from sub-Saharan Africa (FISSA). The aim of this cross-sectional study was to investigate the malaria related-knowledge, attitude and practices (KAP) of FISSA in Edmonton, where these immigrants are in an official minority language situation and the impact of language barriers on these factors. Methods A structured survey was used to examine the KAP of 382 FISSA in the Edmonton area from 2018 to 2019. Fisher’s Exact Test was applied to determine if there were associations between knowledge of malaria and different risk factors. Results Almost all FISSA (97%) had an accurate knowledge of fever as the key symptom of malaria. Interestingly, 60% of participants identified bed nets as a preventive method and only 19% of participants had accurate knowledge of malaria transmission. An accurate knowledge of symptoms was significantly associated with a high perceived risk of contracting malaria [odds ratio (OR) 4.33, 95% confidence interval (CI) 1.07–20.62]. Furthermore, even though 70% of FISSA had a high perceived risk of contracting malaria in endemic regions, only 52% of travellers had a pre-travel medical encounter. Importantly, language was not the predominant reason for not seeking pre-travel medical advice, although 84% of respondents chose French as their official language of preference when seeking medical advice. Having a French-speaking physician was correlated with satisfactory prevention knowledge (OR 1.96, 95% CI 1.16–3.35). With respect to health-seeking behaviour, 88% of respondents with a child < 5 years of age would seek medical care for fever in the child after travel to sub-Saharan Africa (SSA). Conclusion This study highlights that factors other than knowledge, risk assessment, and language might determine the lack of compliance with pre-travel medical encounters. It underscores the need for effective strategies to improve this adherence in minority settings.

Le parcours d’intégration socioéconomique des nouveaux arrivants francophones à Ottawa : quels effets sur la santé? - Kouyé, Jean-Marie; Soulière, Marguerite (Reflets, 2018)
L’intégration socioéconomique constitue l’une des difficultés majeures auxquelles sont confrontés les immigrants, en particulier les nouveaux arrivants francophones. Dès leur arrivée à Ottawa, ces personnes diplômées ayant des expériences de travail sont confrontées au chômage et à la précarité économique. Cet article prend appui sur une recherche qualitative qui s’est intéressée aux parcours d’intégration socioéconomique et à leurs effets sur la santé de nouveaux arrivants (trois hommes et trois femmes). En se référant au cadre conceptuel des déterminants sociaux des inégalités sociales de santé (OMS, 2010), les analyses font ressortir les liens étroits entre l’expérience subjective des nouveaux arrivants francophones à Ottawa, les obstacles rencontrés en matière d’emploi, de revenu et de logement, et l’exposition de ces derniers à des conditions qui les rendent injustement plus exposés à des circonstances de vie qui affectent leur bien-être et leur santé. Par ailleurs, l’étude ouvre sur les perspectives émiques de la santé et du bien-être des participantes et participants, ce qui comporte des pistes significatives pour de futures recherches-interventions en travail social. Mots-clés : immigration francophone, intégration socioéconomique, nouvel arrivant, santé, inégalités sociales, emploi, logement, précarité, recherche qualitative

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)

Linguistic mortality gradients in Quebec and the role of migrant composition - Lo, Ernest; Tu, Mai Thanh; Trempe, Normand; Auger, Nathalie (Canadian Journal of Public Health, 2018)
Objective Anglophones and Allophones in Quebec (Canada) have lower mortality than Francophones, despite being linguistic minorities. This study assesses whether (1) language is a risk factor for mortality after accounting for migrant composition and (2) interprovincial migrants differ in mortality with respect to Quebec-born individuals. Methods We analyzed death records between 2004 and 2008 from Quebec (all-cause and main causes) and population data from the 2006 census to estimate age-adjusted mortality rates according to language and migrant status. Risk ratios by language and migrant status, adjusted for age, sex, and socioeconomic status, were estimated using Poisson generalized estimating equations. Results Francophone Quebec-borns had the highest mortality. Among Quebec-borns, Anglophones [RR= 0.85, 95% CI (0.79–0.91)] and Allophones [RR = 0.16, 95 %CI (0.12–0.22)] had lower mortality relative to Francophones. Interprovincial migrants had lower mortality (Anglophones [RR = 0.58, 95% CI (0.53–0.63)], Francophones [RR = 0.55, 95% CI (0.50–0.60)]) relative to Francophone Quebec-borns (Allophones were excluded due to small sample size). Among immigrants, mortality was lower for Francophones [RR = 0.62, 95% CI (0.57–0.67] and Allophones [RR = 0.35, 95% CI (0.31–0.38], but not Anglophones [RR = 0.92, 95% CI (0.84–1.01)], relative to Francophone Quebec-borns. Conclusion In Quebec, linguistic disparities in mortality remained after accounting for migrant status, and both Francophone and Anglophone interprovincial migrants in Quebec had lower mortality than Quebec-born Francophones. Public health initiatives to reduce linguistic disparities in health should account for migrant status.

Experiences of French speaking immigrants and non-immigrants accessing health care services in a large Canadian city - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda. R.; Musto, Richard; Quan, Hude; King-Shier, Kathryn. M. (International Journal of Environmental Research and Public Health, 2012)
French speakers residing in predominantly English-speaking communities have been linked to difficulties accessing health care. This study examined health care access experiences of immigrants and non-immigrants who self-identify as Francophone or French speakers in a mainly English speaking province of Canada. We used semi-structured interviews to gather opinions of recent users of physician and hospital services (N = 26). Language barriers and difficulties finding family doctors were experienced by both French speaking immigrants and non-immigrants alike. This was exacerbated by a general preference for health services in French and less interest in using language interpreters during a medical consultation. Some participants experienced emotional distress, were discontent with care received, often delayed seeking care due to language barriers. Recent immigrants identified lack of insurance coverage for drugs, transportation difficulties and limited knowledge of the healthcare system as major detractors to achieving health. This study provided the groundwork for future research on health issues of official language minorities in Canada. Keywords: immigrants; French language; health care access; family doctor; qualitative descriptive; official language minorities

Sense of belonging and social climate in an official language minority post-secondary setting - Penner, Kailey; de Moissac, Danielle; Rocque, Rhéa; Giasson, Florette; Prada, Kevin; Brochu, Paul (Canadian Journal of Higher Education, 2021)
Perceived sense of belonging and positive social climate on campus are crucial elements for post-secondary students, as they contribute to academic achievement, positive mental health, and help-seeking. Few studies have explored post-secondary students’ sense of belonging and perceptions of social climate in an official language minority campus, which attract Canadian-born francophones, anglophones who pursue higher education in their second language, and francophone international students. With declining student mental health and greater ethnolinguistic diversity of post-secondary students on Canadian campuses, this important study aims to explore francophone students’ perceived sense of belonging and social climate on campus. In total, 35 students from different ethnolinguistic backgrounds took part in focus groups or individual interviews. Domestic students with French as their first language more often reported positive social climate on campus and a sense of belonging, in contrast to international students and students with French as a second language. A common obstacle to connecting with others was language insecurity in one of the official languages, as both are currently used on campus. Universities hosting students of multiple linguistic diversities should provide courses and campus events to stimulate intercultural knowledge and dialogue.

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)

Language proficiency, gender and self-reported health: An analysis of the first two waves of the longitudinal survey of immigrants to Canada - Pottie, Kevin; Ng, Edward; Spitzer, Denise; Mohammed, Alia; Glazier, Richard (Canadian Journal of Public Health, 2008)
Background Most immigrants to Canada now come from Asia, the Middle East, the Caribbean and Africa, where cultures and languages often differ significantly from the Canadian context. Subgroups of immigrants experience disparities in health. Inability to communicate in an official language in Canada may be a marker of risk for poor health due to both pre- and post-migration factors. We aimed to study the relationship between language proficiency and self-reported health. Methods We conducted a cross-sectional analysis of the first two surveys of the Longitudinal Survey of Immigrants to Canada (2001, 2003), a population-based cohort study of new immigrants to Canada. Specifically, we used logistic regression analyses to examine the relationship between self-reported health and language proficiency by sex, controlling for a range of health determinants at 6 months (wave 1) and 2 years (wave 2) after arrival. Results After controlling for covariates (age, sex, education, region of birth, immigrant class, job satisfaction, access to health care), analysis of the wave 1 survey showed that poor proficiency in English or French is significantly related to the self-reported poor health (OR=2.0, p<0.01). And this relationship was consistent in the wave 2 survey (OR=1.9, p<0.01). We also found that this statistically significant association between poor language proficiency and self-reported health holds only for women (wave 1 survey OR=2.6, p <0.01, wave 2 survey OR=2.2, p<0.01), not for men. Conclusion The association between poor language proficiency and poor self-reported health, and particularly its significantly greater impact on women, has implications for language training, health care and social services, and health information.

Immigration et santé. Où en sont les Francophones ? Une enquête sur l'état de santé des immigrants francophones en Colombie-Britannique - Poullos, Nichollos (RésoSanté Colombie-Britannique, 2018)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Améliorer l’état de santé des francophones de Terre Neuve-et-Labrador - Réseau Santé en français de Terre-Neuve-et-Labrador (2021)

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Centre de recherche en santé dans les milieux ruraux et du nord, 2020)

Communauté immigrante francophone du Grand Sudbury : un état des lieux des services disponibles et des besoins d'accueil. Principaux résultats du rapport technique - Sanou, Boroma; Gauthier, Alain P.; Hien, Amélie; Michel, Isabelle; Timony, Patrick (Santé Canada et Consortium national de formation en santé - Volet Larentienne et Volet Boréal, 2020)

Potential for patient-physician language discordance in Ontario - Sears, Jennifer; Khan, Kamran; Ardern, Chris . I.; Tamim, Hala (BMC Health Services Research, 2013)
Background Patient-Physician language discordance occurs when the patient and physician lack proficiency in the same language(s). Previous literature suggests language discordant clinical encounters compromise patient quality of care and health outcomes. The objective of this study was to quantify and visualize the linguistic and spatial mismatch between Ontario’s population not proficient in English or French but proficient in one of the top five non-official languages and the physicians who are proficient in the same non-official language. Methods Using data from the 2006 Canadian census and the 2006 Canadian Medical Directory, we determined the number of non-English/non-French (NENF) speaking individuals and the number of Ontario physicians proficient in the top five non-official languages in each census division (CD) of Ontario. For each non-official language, we produced bi-variate choropleth maps of Ontario, broken down into the 49 CDs, to determine which CDs had the highest risk of language discordant clinical encounters. Results According to the 2006 Canadian census, the top five non-official languages spoken by Ontario’s NENF population were: Chinese, Italian, Punjabi, Portuguese and Spanish. For each of the top five non-official languages, there were at least 5 census divisions with a NENF population speaking a non-official language without any primary care physicians proficient in that non-official language. The size of NENF populations within these CDs ranged from 10 individuals to 1,470 individuals. Conclusions Understanding the linguistic capabilities of Ontario’s immigrant population & the linguistic capabilities of Ontario’s primary care physicians is essential to ensure equal access and quality of healthcare. As immigration continues to increase, we may find that the linguistic needs of Ontario’s immigrant population diverge from the linguistic capabilities of Ontario’s primary care physicians. Further research on the language discordance in Ontario is needed in order to reduce the risk of language discordant clinical encounters and the negative health outcomes associated with these encounters.

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)

Health profile of linguistic communities in Québec - Tu, Mai. Thanh; Lussier, Marie-Hélène.; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)

Portrait de santé des communautés linguistiques du Québec - Tu, Mai Thanh; Lussier, Marie-Hélène; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the  increase  in  international  mobility,  healthcare  systems  should  no  longer  be  ignoring  language  barriers.  In  addition  to  the  benefit  of  reducing  long‐term  costs,  immigrant‐friendly  organizations  should  be  concerned  with  mitigating  the  way  language  barriers  increase  individuals’  social  vulnerabilities  and  inequities  in  health  care  and  health  status.  This  paper  reports  the  findings  of  a  qualitative,  exploratory  study  of  the  health  literacy  of  28  Francophone  families  living  in  a  linguistic‐minority  situation  in  Canada.  Analysis  of  interviews  revealed  that  participants’  social  vulnerability,  mainly  due  to  their  limited  social  and  informational  networks,  influenced  the  construction  of  family  health  literacy.  Disparities  in  access  to  healthcare  services  could  be  decreased  by  having  health  professionals’  work  in  alliance  with  Francophone  community  groups  and  by  hiring  bilingual  health  professionals.  Linguistic  isolation  and  lack  of  knowledge  about  local  cultural  organizations  among  Francophone immigrants  were  two  important  findings  of  this  study.